Word-of-Mouth System Implementation and Customer Conversion: A Randomized Field Experiment - Huang, Ni; Sun, Tianshu; Chen, Peiyu; Golden, Joseph M. (Information Systems Research, 2019)
Online retailers often face the decision on whether they should implement a word-of-mouth (WOM) system on their websites. Some retailers opt not to have an in-site WOM system (e.g., Tiffany.com and Tjmaxx.com ), whereas others implement and manage an internal WOM system (e.g., Amazon.com and Macys.com ). According to a new study in Information Systems Research, authors Ni Huang (Arizona State University), Tianshu Sun (University of Southern California), Peiyu Chen (Arizona State University), and Joseph M. Golden ( Collage.com ) conducted a randomized field experiment to examine how implementing an in-site WOM system from ground zero influences customer conversion in an online retailing website. Their results demonstrate that implementing an in-site WOM system can be a double-edged sword to the online retailing website. Specifically, the impact of a WOM system implementation on customer conversion is moderated by WOM volume, such that its effect is positive above a threshold of volume and negative below the threshold. Additionally, the researchers find that WOM valence reinforces the impact of a WOM system on customer conversion. These results offer important implications for the hundreds-of-billion-dollar online retailing industry on the implementation and management of online WOM systems.